Conectividad vial en la gestión territorial: una mirada desde los indicadores sociales - Aronés Cisneros, Angel; Córdova Domínguez, Franck Bryan; Sánchez Arias, Lizbeth Gesenia; Vilela Aguilera, Brayan Pooll; Sánchez Vásquez, César Julio; Anampa Huanca, Luz Marina; Melgar Aliaga, Kevin Celso; Mendoza Ramírez, Franz Antony; Montellanos Cabrera, Harry Frank; Bautista Salazar, Edinsson Manuel (Pontificia Universidad Católica del Perú, 2024)
The objective of this research is to analyze road connectivity in relation to the indicators of illiteracy, malnutrition, homes without access to water, non-monetary poverty and internet access. In the methodology for mapping road connectivity, distance weighting or inverse distance weighting (IDW) was used in the ArcGis 10.8 software, while the indicators for the districts have been extracted from GeoPerú. The results indicate that road connectivity plays a crucial role in the socio-economic development of the districts. Those with high connectivity, such as Moche, Huancán and Perené, have lower rates of illiteracy, malnutrition, homes without access to drinking water, non-monetary poverty and homes without internet compared to districts with low connectivity, such as El Porvenir, Santo Domingo de Acobamba and Pichanaqui. It is concluded that road infrastructure is a key factor in reducing inequality and improving living conditions in less developed areas.

El objetivo de esta investigación es analizar la conectividad vial en relación con los indicadores de analfabetismo, desnutrición, viviendas sin acceso al agua, pobreza no monetaria y acceso a internet. En la metodología, para la elaboración cartográfica de conectividad vial, se utilizó la ponderación por distancia o inverse distance weighting (IDW) en el software de ArcGis 10.8, en tanto los indicadores para los distritos se han extraído desde GeoPerú. Los resultados indican que la conectividad vial desempeña un papel crucial en el desarrollo socioeconómico de los distritos. Aquellos con una alta conectividad, como Moche, Huancán y Perené, presentan índices más bajos de analfabetismo, desnutrición, viviendas sin acceso a agua potable, pobreza no monetaria y hogares sin internet en comparación con los distritos de baja conectividad, como. El Porvenir, Santo Domingo de Acobamba y Pichanaqui. Se concluye que la infraestructura vial es un factor clave para reducir la desigualdad y mejorar las condiciones de vida en áreas menos desarrolladas.
Road Connectivity in Territorial Management: A Look from Social Indicators
Keywords: Territorial Management; Cartography; Road Connectivity; Social Indicators; Gestión territorial; Cartografía; Conectividad vial; Indicadores sociales; https://purl.org/pe-repo/ocde/ford#5.07.00